Penyuluhan Kesehatan Reproduksi pada Remaja di SMAN 1 Poigar Bolaang mongondow - Atik Sunarmi; Endang Puji Ati; Sri Atikah (Universitas 45 Surabaya, 2023)
Adolescence is the stage between childhood and adulthood. This period is also called puberty which is the connecting period between childhood and adulthood. Counseling is a form of effort to provide non-formal education to individuals or community groups which is carried out in a systematic, structured, planned and directed manner in an effort to change sustainable behavior. in order to achieve increased production, income and improved welfare. The aim is to increase teenagers' knowledge of information related to reproductive health so they can behave healthily. As a result of this activity, there are still some teenagers who do not understand the importance of maintaining health during adolescence, so it is hoped that by carrying out this counseling, teenagers will increase the interest and awareness of participants to participate in health education. Increase participants' knowledge about the importance of maintaining reproductive health during adolescence.